Gene Expression and Molecular Characterization of a Xylanase from Chicken Cecum Metagenome - Hind AL-Darkazali; Vithaya Meevootisom; Duangnate Isarangkul; Suthep Wiyakrutta (International Journal of Microbiology)
A xylanase gene xynAMG1 with a 1,116-bp open reading frame, encoding an endo-β-1,4-xylanase, was cloned from a chicken cecum metagenome. The translated XynAMG1 protein consisted of 372 amino acids including a putative signal peptide of 23 amino acids. The calculated molecular mass of the mature XynAMG1 was 40,013 Da, with a theoretical pI value of 5.76. The amino acid sequence of XynAMG1 showed 59% identity to endo-β-1,4-xylanase from Prevotella bryantii and Prevotella ruminicola and 58% identity to that from Prevotella copri. XynAMG1 has two conserved motifs, DVVNE and TEXD, containing two active site glutamates and an invariant asparagine, characteristic of GH10 family xylanase. The xynAMG1 gene without signal peptide sequence was cloned and fused with thioredoxin protein (Trx.Tag) in pET-32a plasmid and overexpressed in Escherichia coli Tuner™(DE3)pLysS. The purified mature XynAMG1 was highly salt-tolerant and stable and displayed higher than 96% of its catalytic activity in the reaction containing 1 to 4 M NaCl. It was only slightly affected by common organic solvents added in aqueous solution to up to 5 M. This chicken cecum metagenome-derived xylanase has potential applications in animal feed additives and industrial enzymatic processes requiring exposure to high concentrations of salt and organic solvents.